Pathological Findings in Eurasian Otters (Lutra lutra) Found Dead between 2015−2020 in Schleswig-Holstein, Germany - Simon Rohner; Peter Wohlsein; Ellen Prenger-Berninghoff; Christa Ewers; Patrick Waindok; Christina Strube; Christine Baechlein; Paul Becher; Dunja Wilmes; Volker Rickerts; Ursula Siebert (Animals, 2021)
In times of massive biodiversity loss and ongoing environmental crises, it is extremely important to ensure long-term conservation efforts of threatened species like Eurasian otters (Lutra lutra). To gain insights into the status of Northern Germany’s otter population, 92 otters found dead in Schleswig-Holstein between 2015−2020 were collected and underwent detailed dissection with the aim to establish a monitoring program for this population. Examinations followed a protocol especially designed for otters, including various biological data assessments and extended sampling. The finding sites showed a clear concentration in the Continental region. Seasonal concentration differed among the years, yet peaks were seen from fall to winter. Overall, more males than females were found, although this differed among the years. The majority of otters that could be aged were between 1–3 years. Placental scars and pregnancy were recorded in only few females. Nutritional status was good in most cases. Infectious diseases found included Vagococcus lutrae, Toxoplasma gondii, and Emmonsia spp. A major cause of death was roadkill. Known sample bias in studies focusing on roadkill was considered in the finding interpretation. Continuation of the population health investigations is mandatory to analyze potential trends and to establish an actual monitoring program for Eurasian otters in Schleswig-Holstein.